A biodiversity assessment of hard corals in dive spots within Dampier Straits Marine Protected Area in Raja Ampat, West Papua, Indonesia - YUANIKE YUANIKE; FREDINAN YULIANDA; DIETRIECH G BENGEN; ROKHMIN DAHURI; JEMMY SOUHOKA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Yuanike, Yulianda F, Bengen DG, Dahuri R, Souhoka J. 2019. A biodiversity assessment of hard corals in dive spots within Dampier Straits Marine Protected Area in Raja Ampat, West Papua, Indonesia. Biodiversitas 20: 1198-1207. Hard coral dominates coral reef ecosystems and has important functions and interactions in communities of marine biota. The structure and diversity of hard coral communities is very important to quantify, especially for the management of coral reef ecosystems. The purpose of this research is to identify the diversity of hard coral types, and quantify the condition of hard coral and their distributions in 10 marine stations in Dampier Straits Marine Protected Areas, Raja Ampat. The research method used was line intercept transects measured at two depths, 3 m and 6 m. The results showed there were 141 hard coral species included in 16 families. The percentage live cover of hard coral was in good conditions with an overall average coverage value of 64,24%. The biodiversity index (H) ranged from 0,84-1,23, the evenness index of species ranged from 0,73-0,94, and the species dominance index ranged from 0,05-0,25, indicating a high biodiversity and a lack of dominance by a single species. Although cover was slightly higher at 3m depth, diversity was slightly higher at 6m depth. In general, the 10 research stations in Dampier Straits has hard coral in good condition and the diversity of hard coral species is very productive and has stable growth compared with other sites in Indonesia.